Prognostic factors for musculoskeletal sickness absence and return to work among welders and metal workers. Issue 7 (July 1998) - Burdorf, A; Naaktgeboren, B; Post, W
Abstract : OBJECTIVES: To analyse factors that determine the occurrence of sickness absence due to musculoskeletal problems and the time it takes to return to work. METHODS: A longitudinal study with two year follow up was conducted among 283 male welders and metal workers. The survey started with a standardised interview on the occurrence of musculoskeletal complaints. 61 (22%) workers were lost to follow up. Data on sickness absence among 222 workers during the follow up were collected from absence records and self reports. Regression analysis based on proportional hazards models was applied to identify risk factors for the occurrence and duration of sickness absence due to various musculoskeletal complaints. RESULTS: During the follow up 51% of the workers attributed at least one period of sickness absence to musculoskeletal complaints which accounted for 44% of all work days lost. A history of back pain was not associated with sickness absence for back pain, partly because subjects with back pain were more likely to be lost to follow up. Neck or shoulder pain and pain of the upper extremities contributed significantly to neck or shoulder absence (relative risk (RR) 3.35; 95% confidence interval (95% CI) 1.73 to 6.47) and to upper extremities absence (RR 2.29; 95% CI 1.17 to 4.46), respectively. Company and job title were also significant predictors for sickness absence due to these musculoskeletal complaints. Absence with musculoskeletal complaints was not associated with age, height, body mass index, smoking, and duration of employment. Return to work after neck or shoulder absence was worse among metal workers than welders (RR 2.12; 95% CI 1.08 to 4.17). Return to work after lower extremities absence was strongly influenced by visiting a physician (RR 11.31; 95% CI 2.94 to 43.46) and by musculoskeletal comorbidity (RR 2.81; 95% CI 1.18 to 6.73). CONCLUSIONS: Complaints of the neck or shoulder and upper extremities in the 12 months before the study were associated with sickness absence for these complaints during the follow up. Workers with absence due to pain from back, neck or shoulder, upper extremities, or lower extremities were at higher risk of subsequent sickness absence in the next year.